Not all DTC patients with N positive disease deserve the attribution "high risk". Contribution of the MSDS trial. Issue 1 (12th June 2015) - Vrachimis, Alexis; Wenning, Christian; Gerß, Joachim; Dralle, Henning; Vaez Tabassi, Mohammad; Schober, Otmar; Riemann, Burkhard; on behalf of the MSDS study group
Abstract Background and Objectives To investigate if patients with thyroid carcinoma having N1a disease are at the same risk with N1b using the collective of the well‐defined European prospective Multicentre Study Differentiated Thyroid Cancer (MSDS). Methods Overall (OS) and event free survival (EFS) were calculated. Cox multivariable regression analysis was performed in order to calculate Hazard ratios (HR). Results EFS was significantly decreased only in patients with N1b metastasis as compared to N0 patients and became worse when N1a was concomitantly affected. A superior survival in favor of N1a patients as compared to N1b patients with regard to EFS was also observed. The patients having N1a disease showed no differences in the EFS as compared to N0. OS did not differ significantly in any of the groups. There was an increased HR for events with regards to histology, T‐stage, tumor size, UICC stage and cervical lymph node metastasis. Tumor size showed a significantly increased risk for OS. Conclusions Patients with pT3b and pT4a tumors with N1b are of higher risk for relapse, albeit not affecting overall survival. Patients with N1a are of no higher risk. The risk stratification of these patients may be adapted accordingly. J. Surg. Oncol. 2015 111:9–14. © 2015 Wiley Periodicals, Inc.